Double Contrast-Enhanced Ultrasonography in Preoperative T Staging of Gastric Cancer: A Comparison With Endoscopic Ultrasonography - Wang, Liang; Liu, Zhe; Kou, Hongju; He, Huiliao; Zheng, Bo; Zhou, Lingling; Yang, Yan (Frontiers in Oncology, 2019)
Objective：To investigate the clinical value of double contrast-enhanced ultrasonography (DCEUS) in the preoperative T staging of gastric cancer. Methods: This retrospective study consisted of 158 patients with pathologically confirmed gastric cancer. All patients underwent DCEUS(intravenous contrast-enhanced ultrasound combined with oral contrast-enhanced ultrasound) and endoscopic ultrasonography (EUS) before surgery. The findings of the histopathologic examination were considered as gold standard and were retrospectively compared with the results of DCEUS and EUS. Results: The accuracy of DCEUS and EUS in evaluating the T staging of gastric cancer were 82.3％ (T1 62.5％,T2 84.4％,T3 87.9％,T4 91.3％) and 76.6％ ( T1 84.4％,T2 82.2％,T3 72.4％,T4 65.2％) respectively. There was no significant difference between two methods for the overall T staging accuracy (χ2=1.569, P=0.210). But EUS was superior to DCEUS for T1 stage (χ2=3.925, P=0.048) and DCEUS was superior to EUS for T3 stage (χ2 =4.393, P=0.036) and T4 stage (χ2 =4.600, P=0.032). Conclusion: DCEUS is a convenient and noninvasive method with high accuracy, it can be used as the first choice of imaging modality for the T staging of advanced gastric cancer. In early gastric cancer, we should prefer EUS. Two methods are complementary for assessing tumor invasion depth of gastric cancer.